The Kinship Relationship between The Malay Language of Riau and The Sundanese Language A Comparative Historical Linguistic Study - Efendi, Syahrul; Afri, Evan; Dardanila, Dardanila; Dwiwidayati, Dwiwidayati; Meko MBete, Aron (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study aims to reveal the kinship relationship between Riau Malay and Sundanese languages ??seen from some vocabularies similarities. The method used is descriptive qualitative and quantitative with note-taking technique. The research data is formed of vocabulary in BMR and BS obtained from various written sources and informant interviews. Based on 200 Swadesh words for BMR and BS, there are 12,5%, namely 25 identical pairs words. This data proves that BMR and BS are not closely related because the vocabulary similarities are less than 36% or part of the sub-grouping. Vowel relatives couples different by 16 data or about 18%; 3 relatives couples have different pairs of consonants or about 1.5%; 5 relatives couples or about 2.5% who have one syllable difference; and 9 relatives couples or about 4.5% who have one consonant phoneme difference. The results of the study found that the percentage of kinship between the two languages ??was 29% which indicated that the BMR and BS were the languages ??of the family from one family (stock).BMR and BS are thought to be the same prelanguage around 2,856 years ago and are estimated to have started to separate from their parent languages ??in 833 BC (calculated in 2023)